Modelling Consumer Loyalty in Ayurvedic Medicine: A Pathway to Resilient and Sustainable Healthcare Ecosystems - Dr. J. Hemalatha; Dr. Anjel Raj Y; Dr. S. Thowseaf; Dr. N. Rajapriya (The Bioscan, 2026)
Consumer loyalty has emerged as a crucial aspect for the survival of traditional healthcare systems, particularly in the rapidly expanding market of Ayurvedic medicines. This research studies the determinants of consumer loyalty for Ayurvedic medications by studying the impact of word of mouth, price and credibility on consumer loyalty and the impact of customer trust on word of mouth, price and credibility. A structured questionnaire was given to people who had used Ayurvedic medicines in the past as part of a quantitative research design. To get a total of 326 valid responses, people in Chennai were chosen at random. Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modelling (SEM) with AMOS 20.0 were used to confirm the suggested conceptual model. The results show that cost and word of mouth have a big effect on consumer trust. Trust also has a big effect on consumer loyalty. Referrals from other people also have a big direct effect on trust. Credibility has a big effect on trust, but it does not have a clear effect on loyalty. This means that trust is the only thing that connects the two. A mediation analysis shows that consumer trust plays a big role in the connections between affordability, credibility, word of mouth, and customer loyalty. The study contributes to the existing literature on consumer behaviour and healthcare marketing by investigating trust-based relationship models within the setting of traditional medicine. The results imply that from a business point of view, Ayurvedic enterprises should focus on techniques that generate consumer confidence through truthful communication, positive word-of-mouth, transparent quality assurance and affordable costs to retain clients. This study is helpful to develop powerful and long-lasting healthcare systems based on Ayurvedic medicine. Because it shows how to build long-lasting ties with clients.